Detection of p16INK4a (p16) methylation in diffuse large B-cell lymphoma using methylation-specific PCR - Mohd. Ridah, Lailatul Jalilah; Zainuddin, Norafiza (2014)
Diffuse large B-cell lymphoma (DLBCL) is an aggressive malignancy of non-Hodgkin lymphoma, mostly involve lymph nodes. It is the most common lymphoma among adult with median age 70 years.p16is a tumour suppressor gene (TSG) which inhibits cyclin-dependent kinase thus inactivatesRb protein and blockade G1 phase. Silence of p16 induced by DNA methylation epigenetically has been reported as one of the factors toward DLBCL occurrence with varying percentages. Loss of p16 protein causes unregulated cell division which may lead to cancer. In this study, we aim to identify the presence of p16 methylation in DLBCL. DLBCL samples were obtained from two study groups; Kelantan and Pahang states. Methylation-specific PCR (MSP) was utilized to detect p16 methylation using specific primers in 39 formalin-fixed paraffin embedded tissues samples. The PCR products were then visualized on 2% agarose gels. 14 of 34 (41%) samples are found to have p16 methylation.There was no p16 methylation detected in five normal thyroid samples. p16 gene methylation has been detected in almost half of our samples. This could provide data of gene methylation in DLBCL among Malaysian. Thus, more studies should be carried out for further investigation.